Sintesis Hidroksiapatit Dari Limbah Kulit Kerang Lokan (Geloina Expansa) Dengan Metode Hidrothermal - Mohd Fazhlur Arrafiqie; Yelmida Azis; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Hydroxyapatite Ca10(PO4)6(OH)2is a calcium phosphate compound which is bioactive ceramic material with high bioafinitas and the principal inorganic constituent of bones and teeth. Hydroxyapatite (HAp) materials used as bone implants, adsorbents and catalysts. In this research synthesis of hydroxyapatite can be made by using material which is rich of CaCO3 like PCC lokan calm shell with a composition of 99.45% CaCO3. PCC lokan calm shell which has calcium source was synthesized to HAp by hydrothermal process with varied times of the reaction (12 hours, 16 hours, 20 hours) and reaction temperature (140oC, 160oC, 180oC).HAp synthesized result has been analyzed using X-ray Diffraction (XRD), scanning electron microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). The results of FTIR analysis, synthesisof Hap with hydrothermal method through precipitated calcium carbonat (PCC)showedthe formation of hydroxyapatite in the presence of peaks PO43- dan OH-.The highest peakis obtained at reaction temperature 140oC at reaction times of, 12 hours, 16 hours, 20 hours. XRD diffraction results in hydroxyapatite get the highest purity obtained at temperature of 140oCat time of 20 hour with a hexagonal crystal structure. The results of SEM-EDX analysis, show that the morphological form of agglomerates or clumping . The molar ratio of Ca / P of hydroxyapatite which is made from seashells waste through the PCC is 1,58.Keywords: PCC Lokan Calm Shell, pH, Temperature, Hydroxyapatite, Hydrothermal Method.